Equitable Quality Education for Transformative Higher Education in Southern Africa - Diamond, Dziva; Claretah, Makuvire; Pinias, Chikuvadze; Misheck, Mhishi; Young, Mudavanhu (Quality Assurance Practices for Transformative Higher Education in Southern Africa, 2025)
Equitable quality education serves as a cornerstone for achieving transformative higher education in Southern Africa. This approach prioritises inclusivity and aims to address long-standing historical inequalities that have affected access to education for marginalised communities. By ensuring equitable access to educational opportunities, higher education institutions can empower diverse groups of learners and contribute to a more just and cohesive society. Quality assurance is emphasised as a crucial component of transformative education, ensuring that teaching, learning, and research meet high standards and prepare graduates to make meaningful contributions to their communities and the economy. The concept also aligns higher education with broader regional development goals, fostering innovation and addressing pressing socio-economic challenges such as poverty, unemployment, and environmental sustainability. Research and development play a central role in this transformation, enabling institutions to generate solutions to local and global issues while promoting sustainable development. Building robust research capacity and encouraging collaboration among institutions across the region are essential steps toward creating a knowledge-driven society. Additionally, the chapter highlights the importance of sound policy frameworks that guide the transformation of higher education institutions. Policies must prioritise inclusivity, efficiency, and responsiveness to societal needs, ensuring that higher education catalyses positive change. In conclusion, equitable quality education offers a pathway to a transformative higher education landscape in Southern Africa, one that is inclusive, innovative, and deeply responsive to the region's challenges and aspirations. This vision aims to empower individuals and communities while driving social and economic progress. To foster equitable quality education, higher education institutions in Southern Africa should implement inclusive policies, enhance quality assurance mechanisms, and prioritise research that addresses local socio-economic challenges.